Kalibangkang Nature Park - Budiantono, Iqbal Reza; , Dr.Ir Widyastuti Nurjayanti, MT (2016)
The tour has become part of Indonesia society needs most. Not only for the economic group established, middle-class society and the bottom began to look at tourism as a momentous moment of family recreation. According to the Tourism Ministry, the number of domestic tourists by 2014 reach 251 million. Nature turns out to be the attraction for some of the public. Nearly half the public more interested in travelling to a location that is close to nature. The village of Kalibangkang have the potential of natural resources which is quite abundant, good soil, water or karst ecosystem is still awake, that is like rolling hills, streams, waterfalls, forests, rice paddies, fields, natural plant as well as the flora and fauna that lives with the condition of ecosystems survive the village Kalibangkang. The deeper background of planning and designing The Kalibangkang Nature Park. The Kalibangkang Nature Park is a Forest Park located in the village of Kalibangkang and is a conservation effort as well as a container of all the potential of the village Kalibangkang good flora, fauna as well as the local culture in order to meet the needs of modern tourism and can improve the economy of the village kalibangkang. Kalibangkang Nature Park is planned and designed as a tourist area with sarana-prasarana to embody the potential for nature, Art and culture, Local Village Kalibangkang as well as the needs of travellers, by combining the natural environment, Landscape, the circulation, the time building and potential points of area without removing the natural impression. To embody design according to the needs analysis performed beforehand with the early stages of determining the location of site analysis, then the site analysis meiliputi analysis of achievement, topography, hydrology, topography, vegetation, Sun, wind, view, orientation of buildings, circulation and zoning. Further analysis conducted space requirements as well as the magnitude of the space to determine the relationship of the concept of space. Then conducted an analysis of the landscape, the mass and composition analysis of pattern layout mass to determine the concept of landscape, the mass of the building and the mass of the building. From the analysis of the analyses to be found the main concept for the Kalibangkang Nature Park. The main concept in the design of the building in the Kalibangkang Nature Park is a tropical architecture, namely the architecture that adapts to the tropical climate environment conditions. The concept has a philosophy that blends in with the surrounding environment or adapt to the surrounding environment. The concept of mass composition obtained a building adapted from the physical condition of the environment around the site Kalibangkang Nature Park, i.e. such as palm trees, limestone hills and limestone cliffs. As for the concept of pattern layout time used the concept of centralized, linear and cluster by following the shape of the contour of the site Kalibangkang Nature Park.